2019
DOI: 10.1038/s41598-019-46018-w
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the composition and function of bacterial communities during vermicomposting may explain beneficial properties of vermicompost

Abstract: Vermicomposting is the process by which organic waste is broken down through the synergistic actions of earthworms and microbial communities. Although vermicomposting has been shown to effectively reduce organic biomass and generate high-quality fertilizer for plants, little is known about the bacterial communities that are involved in this decomposition process. Since optimization of vermicomposting for commercial use necessitates additional knowledge of the underlying biological processes, this study sought … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
52
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 56 publications
9
52
2
1
Order By: Relevance
“…Our results disagree with previous ndings about the vermicomposting of green wastes, including Scotch broom and different types of grape marc, where bacterial α-diversity increased with vermicomposting 12,[18][19][20]26 . In those studies, the starting material had not previously been processed by an animal gut, and bacterial diversity was low.…”
Section: Resultscontrasting
confidence: 99%
“…Our results disagree with previous ndings about the vermicomposting of green wastes, including Scotch broom and different types of grape marc, where bacterial α-diversity increased with vermicomposting 12,[18][19][20]26 . In those studies, the starting material had not previously been processed by an animal gut, and bacterial diversity was low.…”
Section: Resultscontrasting
confidence: 99%
“…Gómez-Brandón et al [7] recorded such an increase in bacterial alpha-diversity later on, on day 28. Similar findings were found for other parent materials in which epigeic earthworms led to an increase of bacterial diversity during the first stages of vermicomposting [26,[50][51][52]. While steady and significant increases in bacterial richness and diversity of raw grape marc were reported for the duration of the vermicomposting trial by Kolbe et al [25] and Gómez-Brandón et al [7], we observed a reduction in these measurements in the case of distilled grape marc on day 21 ( Figure 4A).…”
Section: Discussionsupporting
confidence: 90%
“…By using sequencing-based microbiome analyses it has enabled us to enhance the throughput, and phylogenetically group and name a larger number of bacterial taxa in the vermicompost microbiome, as recently described for raw grape marc-derived vermicomposts of the cultivars Albariño [25] and Mencía [7]. Moreover, the application of high-throughput sequencing approaches has also facilitated the identification of bacterial taxa that drive keystone functions that may explain the beneficial effects of vermicomposts when applied to the soil and plants [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Vermicomposting of the Mencía grape marc was carried out in a rectangular metal pilot-scale vermireactor (4 m long × 1.5 m wide × 1 m high) housed in a greenhouse with no temperature control. Further details about the vermireactor set-up and the sampling procedure are given in [27,29]. Briefly, the vermireactor contained a base layer of vermicompost (12 cm height) as a bed for the earthworms prior to adding the grape marc.…”
Section: Methodsmentioning
confidence: 99%